PENGARUH WORKLOAD, WORK MOTIVATION DAN WORK ENGAGEMENT TERHADAP JOB SATISFACTION PADA GURU SMK DI JAKARTA PUSAT - Tia Novitasari; Widya Parimita; Christian Wiradendi Wolor (Lafadz Jaya Publisher, 2023)
The study aims to determine the effect of workload, work motivation and work engagement on job satisfaction at vocational school teachers in the Central Jakarta. The population in this study amounted to 159 respondents and the sample criteria in this study are teachers who are active, have the status non-civil servants and teach at the vocational school (Vocational High School) both public and private located in Central Jakarta. This study uses quantitative approach using non probability sampling teachniques and purposive sampling methods. The number of samples used in this study as many 132 respondents who have a minimum of one year of teaching. This study uses SEM (Structural Equation Modeling) data analysis model by using SmartPLS version 4.0.9.2. The results found in this study indicate that there is a negative and significant influence between variables workload on job satisfaction, then work motivation has a positive and significant effect on job satisfaction and work engagement has a positive and significant effect on job satisfaction.